In-depth analysis of the current state of knowledge on lead-telluride glasses and their properties: Synthesis and characterization of lead-based tellurite glasses and their spectroscopic properties (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Significant amounts of research on glasses have been focused on complicated glasses liketellurite and phosphotellurite as their principal research topics since the 1960s and 1970s. As is the casewith glasses containing tellurium dioxide, well-known glasses also incorporate additional cations asmatrix modifiers, as is also the case with glasses containing tellurium dioxide. Numerous researchershave investigated the spectroscopic properties of rare earth ions found in tellurite glasses. Theinvestigation by comparing and contrasting the optical spectra of Pr3+, Nd3+, Eu3+, Ho3+, and Er3+ in Na2OTeO2glasses with those of the same species in silicate and fluoroberyllate glasses. After making thediscoveries that the activator-ligand interaction in tellurite is more covalent than the interaction influoroberyllate glass, that tellurite's site symmetry is lower than that of fluoroberyllate glass, and thattellurite's average crystal field at the rare earth site is lower than that of silicate glasses, they came to theconclusion that tellurite is the more advantageous material. The literature review of this study wascarried out by screening various global data sets including the web of science, Scopus, PubMed, NIHlibrary and Science Direct. The main aim of this study was to assemble and categorize the synthetic andcharacteristic properties of lead based telluride glasses.